Microstructural and thermal characteristics of the sintered Al-Fe2O3 composites - Boutouta, Aziza (Array, 2020)
This work has as an objective a study of evolution of characteristic properties of crystalline microstructure and mechanical hardening of aluminum by iron oxide (III), (hematite α-Fe2O3) nan energetic material known as thermite, samples of massive alloys, Al (base)-X wt% Fe2O3 (X =2, 4, 16 and 40) were studied.Al-Fe2O3 composite was developed by a sintering technique from the mixtures of compacted powders of Al high purity and α-Fe2O3 under a temperature of 700 °C for 1 hour and then slowly cooled. We have not noted the formation of thermite as foreseen by the chemical reaction due to the mixture of aluminum with hematite. The evolution of crystalline microstructures and the morphologies of surface were determined by means of X-ray diffraction, thermal analysis and optical metallography. The mechanical behavior was characterized by the tests of Vickers indentation and corrosion resistance by electrochemical tests.